2020
DOI: 10.3389/fvets.2020.00081
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Egg Production in the Etiology of Keel Bone Damage in Laying Hens

Abstract: Keel bone fractures and deviations belong to the most severe animal welfare problems in laying hens and are influenced by several factors such as husbandry system and genetic background. It is likely that egg production also influences keel bone health due to the high demand of calcium for the eggshell, which is, in part, taken from the skeleton. The high estrogen plasma concentration, which is linked to the high laying performance, may also affect the keel bone as sexual steroids have been shown to influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 64 publications
4
68
0
Order By: Relevance
“…The association between egg production and keel bone fracture is supported by the absence of fractures in males [ 27 ]. Further evidence of a link between egg production and fractures was gained in a controlled trial where egg production was suppressed completely by deslorelin acetate, resulting in normal, fracture free keel bones [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between egg production and keel bone fracture is supported by the absence of fractures in males [ 27 ]. Further evidence of a link between egg production and fractures was gained in a controlled trial where egg production was suppressed completely by deslorelin acetate, resulting in normal, fracture free keel bones [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…KBF have been found to a varying degree in all major commercial production systems, barren and furnished cages, non-cage systems and organic production [ 11 ]. Compared to cage systems, the prevalence is found to be higher in loose-housed systems [ 12 , 16 , 17 ]. Studies investigating the occurrence of KBF in roosters are generally lacking, but one study reported no cases of KBF in the included roosters [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to cage systems, the prevalence is found to be higher in loose-housed systems [ 12 , 16 , 17 ]. Studies investigating the occurrence of KBF in roosters are generally lacking, but one study reported no cases of KBF in the included roosters [ 16 ]. Welfare implications of KBF include the associated pain [ 18 , 19 , 20 ], reduced mobility [ 21 , 22 , 23 ] and altered affective state [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the spatial distribution of resources in aviary systems, hens cannot avoid applying repeated load on their keel bones when using their flight muscles [ 36 ], and thus have to expose their keel to accumulated forces and corresponding risk for stress fractures when accessing feed, water, nest boxes, perches, or litter. Whereas these forces might not be problematic in healthy hens, weakened bones due to high egg laying rates [ 37 ] or other disease conditions [ 33 ] would contribute to increased fracture susceptibility and the risk for insufficiency fractures (when stress is applied to a bone with deficient elastic resistance [ 16 ]). Second, we found that hens responded differently to perch positioning depending on strain (i.e., brown vs. white hens).…”
Section: Discussionmentioning
confidence: 99%